Anthropometric and strength characteristics of adolescent golfers with low and high handicaps. - Yaping Cao; Ju Li; Zhongcheng Li; Jian Lang (PLoS ONE)
Background The athletic performance of adolescent golfers is influenced by various factors, among which strength qualities and anthropometric characteristics are key. However, current research on these aspects among adolescent golfers with different handicaps remains limited. Objective This study aimed to examine anthropometric and strength characteristics in adolescent golfers of differing handicaps and to explore their relationship with golf performance (handicap). Methods This cross-sectional study recruited 40 adolescent golfers (25 males, 15 females) via convenience sampling, divided into low (n = 20) and high (n = 20) handicap groups. Sample size was determined by a priori power analysis. Anthropometric measures (height, shoulder width, hip, thigh, calf circumferences) and standardized strength tests (grip strength, medicine ball throws, standing long jump, countermovement jump) were assessed. Group differences were analyzed via independent t-tests, and correlations between handicap and strength metrics were analyzed using Pearson's correlation (p < 0.05). Results Golfers with low handicaps demonstrated significantly greater shoulder width (p = 0.033), hip, thigh, and calf circumferences (p < 0.01), and performed better in all strength tests (p < 0.01). Pearson correlation analysis indicated significant negative correlations between handicap and multiple strength metrics (r ranging from -0.324 to -0.556, p < 0.05). Multiple regression analysis showed that strength variables explained approximately 60% of handicap variance. No gender comparisons were conducted. Conclusion Anthropometric advantages and higher strength/explosive power are associated with better performance (lower handicap) in adolescent golfers. It is recommended that training programs for adolescent golfers emphasize strength and explosive power development to improve competitive performance.